Crime and economic incentives - Steve Machin; Costas Meghir (Institute for Fiscal Studies (IFS), 2000)
We explore the role that economic incentives, particularly changes in wages at the bottom end of the wage distribution, play in determining crime rates. We use data on the police force areas of England and Wales between 1975 and 1996. We find that falls in the wages of unskilled workers leads to increases in crime. We carry out a number of experiments with different wage measures, including a wage measure that accounts for the effects of changes in the composition of employment. These reinforce the picture of a strong impact of wages on crime. The result that incentives play a central role is reinforced further by the strong impact on crime of deterrence measures and of a measure of the returns to crime.
Keywords: 330; Kriminalität; Ökonomischer Anreiz; Lohnniveau; Ungelernte Arbeitskräfte; Großbritannien